Accredited retailers' perception of the rice distribution system of National Food Authority in the Province of Negros Occidental - Fidel, Benilda T (Iloilo City U.P. in the Visayas, 2007)
The study aims to assess he rice distribution of NFA based on the accredited retailers' perception. The respondents were the forty (40) accredited retailers particularly in the Bigasan ni Gloria sa Palengke outlets located in major markets of the Province of Negros Occidental. A questionnaire/checklist was used in the gathering of the primary data. The data gathered werethen encoded, tabulated and analyzed using the descriptive statistical tools, such as frequency, distribution and percentage. Most of the retailers are 30-39 years old, female, married, and college graduates. Majority of the respondents have been into grains retailing/wholesaling for21-30 years, have capitalization of P40,000.00 and above and have been NFA accredited retailer from 11-20 years. They sell NFA rice in kilos and their constant buyers are end consumers. They open their stores from 6:00 AM to 6:00 PM seven days a week. Problems encountered by accredited retailers: On accreditation is not being transparent in selection of outlets; On allocation, shortage of weekly allocation; On availability and quantity of stocks, low inventory of stocks during lean months and inferior quality of stocks; On payment of stocks, payment in cash which poses a threat to the retailers' safety and lack of personnel accepting the payment; On withdrawal of stocks, underweighing of stocks was heir major problem; On selling of NFA rice, people's perception of NFA rice as having foul odor and of inferior quality; On NFA employees' performance, employees' being insensitive to the needs of the clientele.Recommendations are hereby presented to address the problems cited. First, NFA rules and regulations must be properly and strictly implemented. Second, to encourage transparency, a representative/president of the retailers association should be invited to sit in the evaluation or re-accreditation of retailers. Third, rice distribution target must be properly studied and planned. Fourth, there should be a thorough inventory of NFA rice for lean months. Fifth, payment of more than p50,000.00 should be in manager;s check t protect the retailers from hold ups. Sixth, platform scale should be properly calibrated. Seventh, massive information campaign on the availability of NFA rice in the market. and lastly, NFA employees should be reminded of their duties and responsibilities as public servant.
"Final report (Research Methods in Management)"